Exploring attitudes to technology adoption for cross compliance in Greek and Lithuanian farmers - Payne-Gifford, Sophie; Johnson, Katherine; Mauchline, Alice; Gadanakis, Yiorgos; Girling, Laura; Mortimer, Simoon (My University, 2020)
The fourth agricultural revolution has started with an explosion of online, smart, digital technologies that are now available to support farmers to improve their operations is enabling opportunities for direct integration between agricultural and computer-based systems. However, the wide range of devices and applications available can be overwhelming and the farming community is showing reluctance to adoption of these new technologies. As part of an EU-funded, multi-partner research project we developed, in collaboration with farmers and other stakeholders, a novel on-line system that supports EU farmers and paying agencies to reduce the administrative burden of CAP’s cross compliance record-keeping and inspections. During the co-development phase we interviewed Greek and Lithuanian farmers about their user needs in relation to the novel system and their potential adoption of this new technology. We analysed their qualitative responses and could identify two groups; ‘Optimistic’ and ‘Reluctant’ in relation to their use of novel technologies. In order to achieve up-take of new technologies within the European farming community, we considered these findings using the Theory of Planned Behaviour and concluded that focussing on the ease of adoption and peer usage would encourage the highest adoption rates as opposed to focusing on changing farmer attitudes.
Keywords: Digital technologies; theory of planned behaviour; co-development; technology adoption